Recent developments and strategies in pediatric pharmacology research in the USA - Vitiello Benedetto (BMC, 2008)
Abstract Research in pediatric pharmacology has undergone major changes in the last ten years, with an expansion in both publicly and privately funded activities. A number of pharmacokinetics studies and multi-site controlled efficacy trials have been conducted, so that treatment of children and adolescents can now be better informed and evidence-based. Regulatory financial incentives to industry in return for studies on drugs still covered by patent exclusivity have resulted in a substantial increase in pediatric research funded by pharmaceutical companies. In parallel, public funding has supported research on off-patent medications and other clinical important aspects of treatment, such as comparisons between active treatments, including non-pharmacological interventions. With greater interest by industry in pediatric research, the role of government funding agencies has been redefined to avoid duplication and ensure better integration of efforts and utilization of resources. The present review discusses some of the recent developments in pediatric pharmacology with focus on psychiatric medications.